Digestible energy content and apparent digestibility coefficients of fish meal, soybean meal, corn, wheat middlings and soybean oil in paiche Arapaima gigas - Vergara-Rubín, Víctor Jesús (2023)
A balanced feed will optimize the performance and nutrient utilization of the paiche according to its genetic potential.  Information is required regarding the nutritive value of the ingredients and the bioavailability of the nutrients. For this reason, and given the limited information available, the objective of this research was to determine the apparent digestibility coefficients of nutrients and digestible energy of fish meal, soybean meal, corn, wheat middlings and soybean oil through the indirect method using chromic oxide as an inert marker. The apparent digestibility of dry matter ranged from 49 % -87 %, protein ranged from 68-90 %, lipids ranged from 73-93 % and energy ranged from 54-97 % for the different ingredients tested. The digestible energy of the fish meal was determined to be 4.34 Mcal.DE/kg. Soybean meal, corn, wheat middlings and soybean oil had values of   3.67 Mcal.DE/kg, 2.63 Mcal.DE/kg, 2.24 Mcal.DE/kg and 9.19 Mcal. DE/kg. Knowledge of the digestibility of nutrients will allow the development of feeds for the paiche with ingredients of greater digestibility, allowing to increase the productive performance of the paiche, the reduction of feeding costs resulting in the improvement of the profitability of fish farmers for a sustainable activity.